EVALUASI PROGRAM BERKAS MLAKU DEWE (BMW) PADA PELAYANAN BIDANG ADMINISTRASI DI KECAMATAN SUKODONO KABUPATEN SIDOARJO - Anisa Anggraeni; Tjitjik Rahaju (Publika, 2022)
Public service is an important activity that must be carried out by the central and local governments to thecommunity in realizing the duties and functions of the government. The Berkas Mlaku Dewe (BMW) Program is a public service program in the field of Electronic Government-based administration, which is a form of government realization based on Sidoarjo Regent Regulation Number 56 of 2018. Evaluation of the BMW program is to determine the success of the program implementation. This type of research is a descriptive study using a literature study method that focuses on evaluating the implementation of the BMW program. The results of the study explain that the BMW application is said to be very effective and efficient due to its fast, easy and transparent service as evidenced by the BMW program being awarded when it was first implemented. On the criteria of adequacy, the BMW application is proven to have satisfied the public. However, the smoothing criteria show that it has not been optimally distributed because there are people who are technologically stuttering. The BMW application has received a good response from the public, because it is seen in SKM which has increased from year to year. This shows that BMW is right for the community even though there are obstacles in the ID card service. The author suggests that the Sidoarjo Regency Government coordinate with Sukodono District to avoid problems with KTP services. The need for optimizing the strength of the internet and intranet networks by the Sukodono District Government to support the implementation of services using the BMW application. Keywords: Evaluation, Berkas Mlaku Dewe, Administration Services